Growth, yield and economic potential of rice (Oryza sativa) as influenced by different age of seedlings, cultivars and weed management under system of rice intensification - SHUKLA, U N; SRIVASTAVA, V K; SINGH, SMITA; SEN, A; KUMAR, V (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted to study the growth, yield and economic potential of rice as influenced by different age of seedlings, cultivars and weed management under system of rice intensification on sandy-clay-loam soil at Agricultural Research Farm of Institute of Agricultural Sciences, Banaras Hindu University during the two consecutive kharif (rainy) seasons of 2010 and 2011. The experiment was laid out in split-plot design with two ages of seedlings with two cultivars assigned to main plots and seven weed management treatments were allocated as sub- plot treatments has replicated thrice. Transplanting of younger age seedling (10 days) of PHB 71 recorded significantly higher growth attributes, viz. plant height, no. of green leaves/hill and dry matter accumulation with yield attributing characters. Similarly, ten days old seedlings of PHB 71 also produced significantly higher yield (grain and straw) that fetched maximum benefit in respect to gross return, net return and B: C ratio over old aged seedling (15 days) of NDR 359 during 2010 and 2011. Among weed management, cono-weeding 4 times at 10, 20, 30 and 40 days after transplanting (DAT) recorded significantly higher growth attributes, yield attributes and yield, but sequential application of pre and post-emergence herbicides, i e pretilachlor + bispyribac-Na was found economically feasible under SRI due to lesser labour requirement.